2022
DOI: 10.3389/fonc.2022.873903
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA Methyltransferase METTL3 in Normal and Malignant Hematopoiesis

Abstract: m6A modification is the most common modification in eukaryotes. METTL3, as a core methyltransferase of m6A modification, plays a vital role in normal and malignant hematopoiesis. Recent studies have shown that METTL3 is required for normal and symmetric differentiation of hematopoietic stem/progenitor cells (HSPCs). Moreover, METTL3 strongly impacts the process and development of hematological neoplasms, including the differentiation, apoptosis, proliferation, chemoresistance, and risk of tumors. Novel inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…The m 6 A writer METTL3, a potential therapeutic target for AML treatment, has recently been reported to promote the initiation and maintenance of AML (15). However, its regulatory mechanisms in AML remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The m 6 A writer METTL3, a potential therapeutic target for AML treatment, has recently been reported to promote the initiation and maintenance of AML (15). However, its regulatory mechanisms in AML remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulating evidence has demonstrated that METTL3 plays critical roles in promoting AML progression as an m 6 A methyltransferase (15,21), it has not been reported whether the E3 ubiquitin ligase can mediate the ubiquitination of METTL3 in AML. To identify METTL3-related E3 ligases, we rst expressed Flag-METTL3 in AML cells and performed mass spectrometric analysis of METTL3-immunoprecipitated complexes from AML cells.…”
Section: Rnf113a Functions As An E3 Ubiquitin Ligase To Mediate Circ_...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, circIGF2BP3 is overexpressed and compromises anti-tumor immunity in NSCLC. METTL3 and METTL14 are composed of a stable methyltransferase complex (MTC) in a 1:1 ratio and exerts a methylation function ( 128 ). Promoting m6A levels in the circIGF2BP3 transcript in a METTL3-dependent manner could enhance the circularization of circIGF2BP3.…”
Section: Interaction Between Ups and Regulatory Ncrnas In Nsclcmentioning
confidence: 99%
“…METTL3 is the most common and most extensively studied methyltransferase of m6A. m6A modifications significantly modulate RNA stability, localization, transport, splicing and translation ( 18 ). METTL3 also plays an integral role in the development and progression of various of tumors.…”
Section: Introductionmentioning
confidence: 99%